SOCIAL CAPITAL BASED ON THE BUDDHIST DHARMA AND THE PROMOTION OF LIFELONG LEARNING IN THE SOCIAL AND CULTURAL CONTEXT OF LOCAL COMMUNITIES IN CHAINAT PROVINCE - Saisena, Natthapat; Nilkote, Reongwit; Sukpom, Thitiwas; Papan, Nattakorn; Charoenlak, Pakporn (Journal of MCU Nakhondhat, 2024)
Social capital based on Buddhist principles serves as a fundamental approach to community development, encouraging people to understand and practice values that emphasize helping others and building a good society. Lifelong learning is a crucial process in developing both individual personalities and communities by equipping people with the necessary knowledge and skills to adapt to new and constantly changing situations. Integrating learning with Buddhist principles enhances the value of learning and links it to personal spiritual growth. Working according to Buddhist principles and promoting lifelong learning requires the active role of local communities, creating spaces and opportunities for community members to engage in activities and projects that foster strength and sustainability. This article aims to present the relationship between Buddhist-based social capital, lifelong learning, and the use of social capital in promoting local community culture and context. An overview of a society based on Buddhist principles highlights living according to moral principles, compassion, and peaceful coexistence. Lifelong learning in the Buddhist way focuses on continuous self-development, guided by the teachings of Buddhism. Promoting learning by utilizing social capital results in strengthened community relationships, connections, and cooperation among individuals, thereby creating a robust and stable community culture. Additionally, promoting lifelong learning leads to the effective application of social capital based on Buddhist principles, resulting in a progressive and morally sound community.